SAE Technical Paper Series 2004
DOI: 10.4271/2004-01-2912
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Engine Oil Vaporization and Transport of the Oil Vapor in the Piston Ring Pack of Internal Combustion Engines

Abstract: A model was developed to study engine oil vaporization and oil vapor transport in the piston ring pack of internal combustion engines. With the assumption that the multi-grade oil can be modeled as a compound of several distinct paraffin hydrocarbons, a set of equations governing the oil vapor density variations were derived by applying the mass conservation law to the amount of oil vaporized from the piston and the amount of oil vapor transported within the piston ring pack.The model was applied to a heavy-du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…The present work has shown that combustion-driven gas flows within the piston crevices can have profound effects on the top land oil film thickness distribution. It has also demonstrated that the multidimensional shock-capturing algorithm described in sections 2 and 3 is successful when applied to nonlinear PDEs of the form of equation (3).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The present work has shown that combustion-driven gas flows within the piston crevices can have profound effects on the top land oil film thickness distribution. It has also demonstrated that the multidimensional shock-capturing algorithm described in sections 2 and 3 is successful when applied to nonlinear PDEs of the form of equation (3).…”
Section: Discussionmentioning
confidence: 98%
“…A distillation curve presented in reference [3] shows that, for some lubricants, the lowest-molecularweight hydrocarbons in the base stock have a lower boiling temperature than 349 uC, and hence can easily be vaporized at such a temperature. In addition to expediting vaporization, high temperatures typically yield an increase in the lubricant's oxidation rate, which is tied to deposit formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation